(untitled) (Economics and region, 2025)
The article under scrutiny herein examines the marketing principles of regional development in the European Union, focusing on their effectiveness and possibilities of adaptation for Ukraine, taking into account current socio-economic and security challenges. The imperatives for implementing European approaches to the use of marketing tools in strategic planning of regional development, attracting investment and improving the economic dynamics of Ukrainian regions are determined. The present study analyses the European practices of regional marketing. Recommendations for adapting the European experience of using marketing tools to the practice of regional development in Ukraine are formulated, including: development of comprehensive regional strategies based on marketing research; creation of unique brands of regions to increase their competitiveness; development of investment platforms to attract investment; activation of public participation through participatory mechanisms; use of digital tools to promote territories. Evidence has been provided to demonstrate that the integration of European practices is an important factor in regional development, especially in the context of Ukraine’s post-war recovery, as it will contribute to economic stability, social cohesion and sustainable development of the territories.